Women and the religion of ancient Israel - Ackerman, Susan (The Anchor Yale Bible Reference Library, 2022)
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Abbreviations -- Introduction -- Part 1. Where? The Sites of Women's Religious Practice -- 1. "Micah's Mother Had Made a Cast-Metal Figurine": Women and Ancient Israelite Household Religion -- 2. "The Women Knead Dough": Women and Ancient Israelite Household Religion -- 3. "She Went Up with Her Husband to Offer the Annual Sacrifice": Women and Ancient Israel's Regional Sanctuaries -- 4. "She Prayed to Yahweh, She Wept . . . and She Made a Vow": Women and Ancient Israel's Regional Sanctuaries -- 5. "This Is the King's Sanctuary and a Temple of the Kingdom": Women and Ancient Israel's State Temples -- 6. "At the Time of Her Menstruation, She Shall Be Unclean": Women and Ancient Israel's State Temples -- Part 2. When? The Calendar of Women's Religious Lives -- 7. "There Is a Yearly Sacrifice . . . for All the Family": The Israelite Woman's Ritual Year -- 8. "You Will Make Three Pilgrimage Journeys to Me": The Israelite Woman's Ritual Year -- Part 3. Who? Women Religious Functionaries -- 9. "When the Young Women of Shiloh Come Out to Dance in the Dances": Women Ritual Musicians in Ancient Israel -- 10. "The Daughters of Your People Who Prophesy": Ancient Israel's Women Prophets -- 11. "Find Me a Woman Who Is a Medium": Ancient Israel's Women Magicians -- 12. "The Sōbě'ôt Who Served at the Entrance to the Tent of Meeting": Determining Their Religious Role -- 13. "The Qe˘dēšâ Among the Daughters of Israel": Defining Her Identity Within the Israelite Cult -- Epilogue -- Notes -- Bibliography -- Index of Subjects -- Index of Modern Authors -- Index of Ancient Sources